Characterization of a Swine Model of Birth Weight and Neonatal Nutrient Restriction. Issue 8 (8th July 2020) - Rodrigues, Lucas A; Wellington, Michael O; Sands, Jade M; Weber, Lynn P; Olver, T Dylan; Ferguson, David P; Columbus, Daniel A
ABSTRACT: Background: Evidence indicates that birth weight and neonatal nutrition have lifelong effects. Animal models are required to improve our understanding of these factors. Objectives: We aimed to develop and validate a swine model of birth weight and neonatal undernutrition. Methods: At birth, a total of 112 piglets were identified as low (LBW; 1.22 ± 0.28 kg SEM) or normal birth weight (NBW; 1.70 ± 0.27 kg). From day 3 to weaning (day 28), piglets received normal nutrition (NN) or restricted nutrition (RN) via intermittent suckling, where piglets were isolated from the sow for 6 h/d. After weaning, pigs were fed a common diet for 28 d. Body weight (BW) was determined for the duration of the study. On days 28 and 56, empty carcass, viscera, and individual organ weights were determined in 8 pigs/treatment. Results: LBW pigs remained smaller than NBW pigs, regardless of nutrient restriction ( P < 0.05). Within birth weight category, RN reduced BW by day 7 after birth, which was maintained until weaning ( P < 0.05); however, at 7 d postweaning there was no difference in BW due to RN ( P > 0.05). At weaning, empty carcass, viscera, heart, liver, and lung weights were lower in LBW than in NBW pigs, whereas empty carcass, heart, small intestine, liver, kidneys, lung, and spleen weights were lower in RN than in NN pigs ( P < 0.05). Brain weight was highest in NBW-NN and lowest in NBW-RN, with LBW intermediate, regardless of nutrient restriction ( P < 0.05). Postweaning, LBW had lower empty carcass, viscera, heart, stomach, large intestine, liver, and kidney weights than NBW, whereas RN had a higher small intestine weight than NN ( P < 0.05). Conclusions: Intermittent suckling is an effective means of inducing nutrient restriction in a swine model. Abstract : We characterize a swine model of birth weight and neonatal undernutrition. We show that both birth weight and nutrition lead to both short- and long-term effects on growth and development.